A method of creating personae for children with autism spectrum condition: application and revision. Issue 2 (17th June 2019) - Zubair, Misbahu S.; Brown, David; Hughes-Roberts, Thomas; Bates, Matthew
Abstract : Purpose: Personae are simple tools for describing users, their characteristics and their goals. They are valuable tools when designing for a specific group of users, such as children with autism spectrum condition (ASC). The purpose of this paper is to propose, validate and revise a methodology for creating accurate, data grounded personae for children with ASC. Design/methodology/approach: The proposed method is based mainly onCooper et al. 's (2007) persona construction method. It proposes gathering and analysing qualitative data from users and experts to either create a new persona or extend an existing one. The method is then applied to create personae for the design of a visual programming tool for children with ASC. Based on the results of the application, observations and lessons learnt, a revised version of the method is proposed. Findings: The method's combined use of user data and expert knowledge produced a set of personae that have been well reviewed by experts so far. The method's use of a questionnaire to validate personae also produced relevant qualitative feedback. On review, possible downsides of extending existing personae were identified. Therefore, a revised method was introduced, eliminating the need to extend existing personae, and stressing the importance of utilising user data, expert knowledge and feedback. Originality/value: This paper addresses the need for a well-defined method for creating data grounded personae that accurately describe the characteristics and goals of children with ASC. Such personae can be used to design and develop more accessible and usable products.